SOIL CHEMISTRY TRENDS - Yu. Vodianitsky (Бюллетень Почвенного института им. В.В. Докучаева)
In modern soil chemistry, four main directions are being actively developed: 1) chemistry of organic matter, 2) biochemical processes in soils, 3) chemical basis of soil protection, 4) soil study aschemical membrane and a pool of chemical elements. Interest to the study of organic matter, soil contamination and the role of soil as a chemical component of the environment reflects pragmatic trends in modern soil chemistry. Many advances in soil chemistry are now associated with the use of new nonspecific methods of analysis, primarily physical ones. The greatest progress has been made inidentification of individual chemical compounds in soil when using synchrotron X-ray technology.